Western European inflation and the reserve currencies - BAFFI, P. (PSL Quarterly Review, 2014)
The article is a text read and discussed at Chatham House, London, in February 1968. The author establishes to what extent and in what ways British monetary policies, and those of the other main reserve currency countries, have interacted with the European Economic Community’s. The analysis is confined to the years following the return to convertibility, starting with 1959 and ending with 1966. Two extreme lines of thought are distinguished, which are so far removed the one from the other as to leave a very wide field of opinion in between. At one extreme, there is the school of thought that maintains that the reserve currency countries have been exporting inflation. At the other extreme, it is claimed that they have been importing, if not actual deflation, at least certain deflationary impulses from the non-reserve currency countries, mainly those in continental Western Europe. The evidence might show that the same kind of impulses emanated from both sets of countries, and that the difference between them was only one of degree. JEL: E31, E52, E42